Debt structure when bankruptcy law offers incentives to restructure - Iftekhar Hasan; Kose John; Padma Kadiyalad (Bank of Finland, 2016)
We augment the LLSV creditor rights index with a new "restructuring index" that measures the incentives provided to creditors to grant concessions outside formal bankruptcy. We study the joint impact of the two indexes on a firm's leverage policy. We show that the two indexes have at most a statistically weak effect on the level of long-term debt. Instead, the two indexes affect the distribution of long-term debt into bank debt, public debt and private placements. Bank debt increases when the values of both indexes are high. Public debt increases when the creditor rights index is high, but the restructuring index is low, and private placements increase when the restructuring index is high, but the creditor rights index is low. Smaller firms with fewer tangible assets borrow more from banks when both the creditor rights and restructuring indexes are high. When aggregated at the country level, these firm-level results suggest that bankruptcy law can influence the relative importance of credit and equity markets as sources of financing GDP growth.
URN:NBN:fi:bof-201605191128
Keywords: G32; G33; G38; 330